Peran Bimbingan dan Konseling dalam Mengurangi Kecanduan Game Online melalui Digital Well Being : A Systematic Literatur Review - Rizka Tyara; Mulawarman Mulawarman; Sunawan Sunawan; Muslikah Muslikah; Ernest Ceti Septyanti (Pusat Riset dan Inovasi Nasional, 2025)
Online game addiction has emerged as a significant concern in the contemporary digital era, particularly among adolescents and students. This condition poses detrimental impacts on psychological well-being, social functioning, and academic achievement. The present study aims to investigate the role of guidance and counseling services in mitigating online game addiction through the lens of digital well-being, employing a Systematic Literature Review (SLR) methodology. Relevant national and international journal articles published within the past decade were systematically analyzed. The findings indicate that guidance and counseling interventions are effective in fostering self-awareness, improving time management skills, and promoting healthy digital behaviors among individuals affected by online gaming addiction. The digital well-being framework serves as a critical foundation for cultivating a more balanced and mindful interaction between individuals and technology. The study concludes by underscoring the necessity of integrating guidance and counseling strategies with digital well-being principles to address online game addiction in a comprehensive and sustainable manner.